anonymous
  • anonymous
Another Algebra Problem! -6(9x - 6) = 306 Help plz!
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
I think i got it. I came up with -5!
anonymous
  • anonymous
-17
anonymous
  • anonymous
-54x+36=306 -54x=270 x=306/(-54) x=-5

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
You didnt distribute .
anonymous
  • anonymous
what?
anonymous
  • anonymous
Solve for x: -6 (9 x-6) = 306 Factor the polynomial, -6+9 x. Factor 3 from the polynomial 9 x-6: -63 (3 x-2) = 306 Multiply -6 and 3 together. -6×3 = -18: -18 (3 x-2) = 306 Divide both sides by a constant to simplify the equation. Divide both sides of -18 (3 x-2) = 306 by -18: (-18 (3 x-2))/(-18) = 306/(-18) Any nonzero number divided by itself is one. (-18)/(-18) = 1: 3 x-2 = 306/(-18) Reduce 306/(-18) to lowest terms. The gcd of 306 and -18 is 18, so 306/(-18) = (18×17)/(18 (-1)) = 18/18×17/(-1) = 17/(-1): 3 x-2 = 17/(-1) Simplify the sign of 17/(-1). Multiply numerator and denominator of 17/(-1) by -1: 3 x-2 = -17 Isolate terms with x to the left hand side. Add 2 to both sides: 3 x+(-2+2) = -17+2 Look for two terms that sum to zero. -2+2 = 0: 3 x = -17+2 Evaluate -17+2. -17+2 = -15: 3 x = -15 Solve for x. Divide both sides of 3 x = -15 by 3: (3 x)/(3) = (-15)/3 Any nonzero number divided by itself is one. 3/3 = 1: x = (-15)/3 Reduce (-15)/3 to lowest terms. The gcd of -15 and 3 is 3, so (-15)/3 = (3 (-5))/(3×1) = 3/3×-5 = -5: Answer: | | x = -5
anonymous
  • anonymous
Hopefully that helps.
anonymous
  • anonymous
A lot Ty :D
anonymous
  • anonymous
@BabyPhoenix just stick with @rajatgang answer

Looking for something else?

Not the answer you are looking for? Search for more explanations.